EULAR points to consider for conducting clinical trials and observational studies in individuals at risk of rheumatoid arthritis. Issue 10 (6th August 2021) - Mankia, Kulveer; Siddle, Heidi J; Kerschbaumer, Andreas; Alpizar Rodriguez, Deshire; Catrina, Anca Irinel; Cañete, Juan D; Cope, Andrew P; Daien, Claire Immediato; Deane, Kevin D; El Gabalawy, Hani; Finckh, Axel; Holers, V Michael; et al.
Abstract : Background: Despite growing interest, there is no guidance or consensus on how to conduct clinical trials and observational studies in populations at risk of rheumatoid arthritis (RA). Methods: An European League Against Rheumatism (EULAR) task force formulated four research questions to be addressed by systematic literature review (SLR). The SLR results informed consensus statements. One overarching principle, 10 points to consider (PTC) and a research agenda were proposed. Task force members rated their level of agreement (1–10) for each PTC. Results: Epidemiological and demographic characteristics should be measured in all clinical trials and studies in at-risk individuals. Different at-risk populations, identified according to clinical presentation, were defined: asymptomatic, musculoskeletal symptoms without arthritis and early clinical arthritis. Study end-points should include the development of subclinical inflammation on imaging, clinical arthritis, RA and subsequent achievement of arthritis remission. Risk factors should be assessed at baseline and re-evaluated where appropriate; they include genetic markers and autoantibody profiling and additionally clinical symptoms and subclinical inflammation on imaging in those with symptoms and/or clinical arthritis. Trials should address the effect of the intervention on risk factors, as well as progression to clinical arthritis or RA. In patients with early clinical arthritis, pharmacological intervention has the potential to prevent RA development. Participants' knowledge of their RA risk may inform their decision to participate; information should be provided using an individually tailored approach. Conclusion: These consensus statements provide data-driven guidance for rheumatologists, health professionals and investigators conducting clinical trials and observational studies in individuals at risk of RA.